2018
DOI: 10.1038/s41598-018-35391-7
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Mitochondrial Activity in the Healing Response Following Rotator Cuff Tendon Injury

Abstract: Mitochondrial function following rotator cuff tendon injury (RCI) influences the tendon healing. We examined the mitochondrial morphology and function under hypoxia in the shoulder tendon tissue from surgically-induced tenotomy-RCI rat model and cultured swine tenocytes. The tendon tissue was collected post-injury on 3–5 (Group-A), 10–12 (Group-B), and 22–24 (Group-C), days and the corresponding contralateral tendons were used as control for each group. There was higher protein expression of citrate synthase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 50 publications
(60 reference statements)
0
31
0
Order By: Relevance
“…21 Another study, by Thankam et al, demonstrated that the expression of two mitochondrial biomarkers, citrate synthase and complex-1, were increased significantly at 3-5 days and 10-12 days after injury in a rat rotator cuff tendon injury surgical model but decreased in the later phase of healing. 31 They also found that the hypoxic tenocytes exhibited an increase in mitochondrial superoxide, altered morphology and mitochondrial pore integrity, and increased mitochondrial density compared with the control group. These findings also support the notion that mitochondrial function may be critical in not only the development of tendinopathic disorders but also the tendon healing response.…”
Section: Mitochondrial Dysfunction In Tendinopathymentioning
confidence: 95%
See 2 more Smart Citations
“…21 Another study, by Thankam et al, demonstrated that the expression of two mitochondrial biomarkers, citrate synthase and complex-1, were increased significantly at 3-5 days and 10-12 days after injury in a rat rotator cuff tendon injury surgical model but decreased in the later phase of healing. 31 They also found that the hypoxic tenocytes exhibited an increase in mitochondrial superoxide, altered morphology and mitochondrial pore integrity, and increased mitochondrial density compared with the control group. These findings also support the notion that mitochondrial function may be critical in not only the development of tendinopathic disorders but also the tendon healing response.…”
Section: Mitochondrial Dysfunction In Tendinopathymentioning
confidence: 95%
“…The pathological impact of hypoxia-induced mitochondrial dysfunction and pro-oxidant responses has been reported to play a critical role in the initiation of rotator cuff tendinopathy. 31 Among the alarmins, HIF1α senses oxygen and is regulated by oxygen availability. 69 Hypoxia induces the translocation of HIF1α into the nucleus in isolated macrophages, 70 indicating that HIF1α activation induces mitochondrial dysfunction, which is reflected by increased ROS, mitochondrial membrane potential, and mitochondrial mass.…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Infraspinatus tendon tissue was aseptically harvested from the shoulder of Yucatan microswine (Sinclair Research) (female, 6–8 months old) from an ongoing study approved by the Institutional Animal Care and Use Committee (IACUC) of Creighton University, Omaha, NE. The tenocytes were isolated following the partial collagenase digestion explant culture standardized in our laboratory 16 . The isolated tenocytes were maintained in DMEM containing 20% FBS and antibiotics at 37°C and 5% CO 2 in a humidified incubator, the media was changed twice a week, passaged at 70–80% confluency, and the cells in passage 2–4 were used for the studies.…”
Section: Methodsmentioning
confidence: 99%
“…The CASMCs were maintained as mentioned above (Control, ISC, and ISC/R) in chamber slides, xed with 10% formalin for 20 min and immuno uorescence of 5LPOX, 12LPOX, 15LPOX, COX2, ChemR23, GPCR18, and GPCR120 were performed [17]. The primary antibodies and uorochrome-conjugated secondary antibodies were diluted 1:400 and 1:500, respectively.…”
Section: Immuno Uorescencementioning
confidence: 99%